2010
DOI: 10.1111/j.1748-1716.2010.02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia preconditioning by cobalt chloride enhances endurance performance and protects skeletal muscles from exercise‐induced oxidative damage in rats

Abstract: Our study provides strong evidence that hypoxic preconditioning with cobalt chloride enhances physical performance and protects muscle from exercise-induced oxidative damage via GSH, HO-1 and MT-mediated antioxidative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 83 publications
(147 reference statements)
1
37
0
Order By: Relevance
“…As ROS are involved in HIF-1a stabilization (see above), this reduction would suppress HIF-1a accumulation consistently with its transient up-regulation observed in vitro [34]. Muscle proteome of highlanders is characterized by reinforced protection against ROS compared to control subjects permanently residing at low altitude [84], and hypoxia preconditioning by CoCl 2 in rats reduced exercise-induced skeletal muscle oxidative damages [85]. Altogether, this confirms that regulation of redox status under reduced O 2 availability is of key importance.…”
Section: Mitochondrial Remodelling and Regulation Of Ros Productionmentioning
confidence: 99%
“…As ROS are involved in HIF-1a stabilization (see above), this reduction would suppress HIF-1a accumulation consistently with its transient up-regulation observed in vitro [34]. Muscle proteome of highlanders is characterized by reinforced protection against ROS compared to control subjects permanently residing at low altitude [84], and hypoxia preconditioning by CoCl 2 in rats reduced exercise-induced skeletal muscle oxidative damages [85]. Altogether, this confirms that regulation of redox status under reduced O 2 availability is of key importance.…”
Section: Mitochondrial Remodelling and Regulation Of Ros Productionmentioning
confidence: 99%
“…Eventually, also the MSC-, HSC-, and EPC-derived mature cells are affected by HO-1. Antiapoptotic, anti-inflammatory, and proproliferative effects of HO-1 were reported in osteoclasts (179,256), osteoblasts (34,41,43), myoblasts (80,168,182), leukocytes (234), and endothelial cells (133).…”
Section: Heme Oxygenase-1mentioning
confidence: 99%
“…Furthermore, strenuous exercise is known to cause oxidative stress and inflammatory responses in skeletal muscles which leads to muscle damage. Previous studies carried out in our laboratory have shown that preconditioning by oral cobalt supplementation, a hypoxia mimetic, enhances endurance performance and also protects muscle from exercise induced oxidative damage in rat skeletal muscle 8 . Most importantly, supplementation of hypoxia mimetics is practical and feasible way of inducing hypoxia to enhance physical performance.…”
mentioning
confidence: 88%